Long-term Follow-up of a Patient with Quadruple Valve Replacement - Hossack, Kenneth F. (1987)
A 60-year-old woman who had suffered from rheumatic fever as a child required replacement of the aortic, mitral, and pulmonary valves. Subsequently, because of severe regurgitation, the tricuspid valve was also replaced. This case proves that, with satisfactory intraoperative cardiac protection, quadruple valve replacement can produce a good long-term functional result. (Texas Heart Institute Journal 1987; 14:315-317)